EXPERIENTIAL LEARNING: AN ANALYSIS OF IMPACT ON ACADEMIC ACHIEVEMENT AMONG STUDENTS OF GRADE 12 - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2020)
The molecular model as a learning tool in class-room instructions is significant due to its positive effect on the learning and teaching process. Many students struggle to learn Chemistry and do not succeed. Chemistry is the central part of all Science subjects. To make Chemistry learning easy and joyful appropriate method of class-room instructions are important. The Chemistry of solid states and composite materials is the part of the curriculum at All India Senior Secondary School Curriculum. Students face problems in solid state Chemistry due to its abstract concepts. To address the issue, handmade models and paper-based models are made as evidence-based learning. In this present paper attempt is made to investigate the impact of handmade paper model of unit cell and crystal lattices of solid-state Chemistry on academic achievement. The study is delimited to the students of only one school in rural area. Totally 50 students participate in the study. Sample is distributed into two groups: study group and the control group, by connecting them on the basis of the previous knowledge which is determined through pre-test. The students of the study group are taught solid states Chemistry through handmade paper models of unit cells and crystal lattices and the students of the control group are taught by using traditional chalk and board method. Data is collected by using Test (Pre and Post). Mean standard deviation and mean differences are used as a statistical tool to analyze the data. Substantial difference between the study group and the control group of mean score on test (pre and post and retention) are tested at 0.05 level. The handmade paper model of unit cell and crystal lattices of solid states Chemistry has significant positive impact on the academic achievement in solid state Chemistry. Based on the findings of the present study, some recommendations are made for using paper model as teaching aid for evidence-based learning in Chemistry and other core subjects to move up the students’ academic performance level.